2019
DOI: 10.22270/jddt.v9i2.2524
|View full text |Cite
|
Sign up to set email alerts
|

Inflammation the Kingpin of Chronic Diseases Naturopathy as an alternative source of treatment: An updated overview

Abstract: Inflammation involves a sequence of events which can be categorized under three phases viz. acute transient phase, delayed sub-acute phase and chronic proliferate phase. Inflammatory mediators develop due to enhanced vascular permeability and leads to local edema. It is followed by the migration of leukocytes and phagocytes from blood to vascular tissues which is the second phase, in the third phase, tissue degradation is followed by fibrosis. There is a powerful link between chronic diseases and chronic infla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 33 publications
(34 reference statements)
0
2
0
Order By: Relevance
“…An intrajugular injection of 2.5 μg/kg LPS resulted in different expressions of inflammation-related genes in ewes [2]. Yates et al [27] reported that an intrajugular injection of 0.75 and 1.5 μg/kg LPS caused a dose-dependent inflammatory response, manifested as an increase in rectal temperature, serum cortisol, and serum insulin. A single injection of LPS in animals only induced a short-term acute immune stress, which caused a sharp increase in plasma concentrations of inflammatory cytokines that returned to the pre-injection levels after 4 to 8 h [2,27,28].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An intrajugular injection of 2.5 μg/kg LPS resulted in different expressions of inflammation-related genes in ewes [2]. Yates et al [27] reported that an intrajugular injection of 0.75 and 1.5 μg/kg LPS caused a dose-dependent inflammatory response, manifested as an increase in rectal temperature, serum cortisol, and serum insulin. A single injection of LPS in animals only induced a short-term acute immune stress, which caused a sharp increase in plasma concentrations of inflammatory cytokines that returned to the pre-injection levels after 4 to 8 h [2,27,28].…”
Section: Discussionmentioning
confidence: 99%
“…Yates et al [27] reported that an intrajugular injection of 0.75 and 1.5 μg/kg LPS caused a dose-dependent inflammatory response, manifested as an increase in rectal temperature, serum cortisol, and serum insulin. A single injection of LPS in animals only induced a short-term acute immune stress, which caused a sharp increase in plasma concentrations of inflammatory cytokines that returned to the pre-injection levels after 4 to 8 h [2,27,28]. Therefore, to reduce the tolerance and avoid the risk of mortality due to LPS in lambs in the present study, an initial dose of 0.25, 1.25, or 2.5 μg/kg LPS was injected every other day with a dose increase of 20% each time to examine the putative effect of resveratrol on inflammatory responses.…”
Section: Discussionmentioning
confidence: 99%